PERANAN LEMBAGA PEMASYARAKATAN DALAM PROSES PEMBINAAN NARAPIDANA DISABILITAS KASUS NARKOTIKA - Manalu, Bernata Rikardo; Subroto, Mitro (Universitas Nusa Cendana, 2024)
This research explores the implementation of rehabilitation programs for disabled drug offenders in Indonesian penitentiary institutions, with a primary focus on the theory of inmate rehabilitation. The study reveals that these institutions provide a comprehensive range of training, encompassing skill development, religious engagement, and behavior rehabilitation. The theory of inmate rehabilitation serves as a vital framework in this process, facilitating positive behavioral transformation and preparing disabled inmates for reintegration into society. Nevertheless, various hindrances, such as staffing imbalances, resource limitations, and inadequate skill development instructors, were identified. Despite these challenges, disabled inmates reported positive outcomes resulting from these drug rehabilitation programs. They expressed readiness to reintegrate into society following their incarceration. These findings underscore the significance of rehabilitation within the criminal justice system, especially for disabled drug offenders. This research serves as a guide for enhancing and expanding drug rehabilitation programs within penitentiary institutions, with the ultimate aim of helping inmates become more productive members of society. Keywords: Rehabilitation Programs; Disabled Drug Offenders; Criminal Justice System